2019
DOI: 10.15171/mejdd.2018.133
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Heller Myotomy for Achalasia: Experience from a Single Referral Tertiary Center

Abstract: BACKGROUND Achalasia is the most well known esophageal motility disorder. Laparoscopic Heller myotomy (LHM) is the most effective treatment for achalasia. The aim of this study was to review our results on LHM for achalasia. METHODS In this cross-sectional study all patients undergoing LHM between 2015 and 2017 were studied. The myotomy was followed by an anterior or posterior partial fundoplication. All patients were followed up for at least six months. RESULTS We conducted this prospective study on 36 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…25 Laparoscopic Heller myotomy (LHM) with a partial fundoplication is the optimal surgical treatment of achalasia, with effective control of symptoms in 90 to 97 percent of patients. 26 This procedure will cut the circular muscle fibers running across the lower esophageal sphincter, leading to relaxation. LHM can potentially cause uncontrolled gastroesophageal reflux, so it typically pairs with an anti-reflux procedure such as Nissen, the posterior (Toupet), or the anterior (Dor) partial fundoplication.…”
Section: Uppermentioning
confidence: 99%
“…25 Laparoscopic Heller myotomy (LHM) with a partial fundoplication is the optimal surgical treatment of achalasia, with effective control of symptoms in 90 to 97 percent of patients. 26 This procedure will cut the circular muscle fibers running across the lower esophageal sphincter, leading to relaxation. LHM can potentially cause uncontrolled gastroesophageal reflux, so it typically pairs with an anti-reflux procedure such as Nissen, the posterior (Toupet), or the anterior (Dor) partial fundoplication.…”
Section: Uppermentioning
confidence: 99%
“…Achalasia is a primary oesophageal motor disorder thought to be caused by autoimmune neuro-degeneration of the oesophageal myenteric plexus. Achalasia is the most well known esophageal motility disorder 1 with an annual incidence of 1 in 100,000 and prevalence of 8 in 10,000 people. The prevalence is equal in men and women.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence is equal in men and women. 1 However, recent studies have shown that the incidence of achalasia is increasing, particularly in South America, and varies among countries. 2 Achalasia has a bimodal age distribution, with most patients aged between either 20-40 or 60-70 years.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of achalasia is not curative. It is a progressive disease that leads patients to seek symptom palliation, which can be accomplished by reducing the resting and swallow-induced pressures of the LES [1,3,[7][8][9][10] . That is, therapy is aimed at relieving the functional obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, minimally invasive Heller myotomy is currently the gold standard surgical approach for achalasia as it has the best long-term outcome. Although per-oral endoscopic myotomy (POEM) and robotic Heller myotomy (RHM) are increasingly being used, laparoscopic Heller myotomy (LHM) is the longest practiced surgical approach with safe and effective outcomes [8,9,[12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%